Utilization of the Alumni Site of SMA Negeri 1 Kelam Permai - Gat Gat; Muhammad Ivansyah Basya; Reika Bulandari (JUDIMAS, 2020)
One who has an important role in school development is alumni, but regarding alumni, many schools have not utilized alumni in school contributions, one of which is SMA Negeri 1 Kelam Permai. So far, the alumni data collection at SMA Negeri 1 Kelam Permai has not been carried out in a structured and online manner. In collecting data on alumni, it is still done by recording in written documents which results in data management cannot be done quickly and errors often occur, and it is difficult to update information about alumni. In carrying out this service, the author uses the lecture method and direct system demonstration to participants. The lecture method is used because it is efficient to interact directly with the participants. While the demonstration method is used to teach participants how to use the system. The purpose of this service is to teach participants how to use a website that can help schools quickly and accurately in the process of collecting data and managing alumni data in obtaining information about alumni.